The Study of Seafloor Tin Placer Resources of Quaternary Sediment at Toboali Waters, South Bangka - Muhammad Zulfikar; Noor CD Aryanto (BULLETIN OF THE MARINE GEOLOGY, 2016)
Bangka Island has primary and secondary tin deposit. However, along the history of tin mining has been done the primary tin deposit domination is less than secondary tin deposit. Secondary tin deposit is formed from Granitic S-type source rock weathering and then transported by gravity. After that, Cassiterite mineral (SnO2) accumulates and forms a placer deposit in the study area. The thickness of sediment cover at Toboali Waters is quite diverse, with a range between 5-20 milliseconds, by knowing the quarter sediment thickness using seismic data interpretation results, is expected to give an idea about tin placer deposit potential in Toboali waters. Based on the Isochron map shows patterns of quaternary sediment thickening to the southwest, south and southeast of Bangka Island.Keywords: Quaternary sediment, placer deposit, isochron map, Toboali WatersPulau Bangka memiliki endapan timah primer dan endapan timah sekunder. Namun, sepanjang sejarah penambangan timah yang telah dilakukan endapan timah primer tidak mendominasi jika dibandingkan dengan endapan timah sekunder. Pembentukan endapan timah sekunder berawal dari pelapukan batuan Granit tipe-S yang kemudian mengalami transportasi akibat adanya gravitasi. Setelah itu, mineral kasiterit (SnO2) terakumulasi dan membentuk endapan plaser di daerah penelitian. Ketebalan sedimen penutup di Perairan Toboali berkisar antara 5-20 milidetik, dengan mengetahui ketebalan sedimen kuarter berdasarkan interpretasi data hasil rekaman seismik diharapkan dapat memberikan gambaran tentang potensi endapan timah placer di Perairan Toboali. Berdasarkan atas peta isokron, memperlihatkan bahwa pola penebalan sedimen kuater ke arah baratdaya, selatan dan tenggara Pulau Bangka.Kata kunci : Sedimen kuarter, endapan placer, peta isokron, Perairan Toboali